ANALISIS KETERCAPAIAN DATA UKUR ROOF DAN FLOOR TERHADAP TOTAL MATERIAL (STUDI KASUS: PT SATRIA BAHANA SARANA) - Kurniawan, Imam; Arini, Dwi; Defwaldi, Defwaldi; Armi, Ilham; Fajrin, Fajrin (Jurnal Spasial, 2025)
Mining comprises activities from exploration to post-closure, including investigation, feasibility studies, construction, extraction, processing, transport, and sales. PT Satria Bahana Sarana operates within PT Bukit Asam Tbk’s concession, performing overburden removal and coal haulage from pit to temporary stockpiles and onward to livestock. Following a 2024 directive from PT Bukit Asam Tbk, all contractors working in the concession must include roof and floor measurement data in production reports. PT Satria Bahana Sarana has faced deviations between roof and floor survey results and actual production records, with field measurements often differing from truck counts and dump hopper volumes. This study quantitatively analyzed the alignment of roof and floor measurements with production data collected from April to September 2024. Numerical datasets were compared and correlations evaluated using Pearson and Spearman methods to measure relationships between survey measurements and production figures obtained from truck counts and dump hoppers. Results indicate a strong positive correlation, with a Pearson coefficient of 0.9137 and a Spearman coefficient of 0.943. These outcomes suggest roof and floor measurements can serve as a reliable basis for production planning and performance evaluation. Implementing rigorous data validation and reconciliation can reduce deviations, improve reporting accuracy, enhance operational efficiency, regulatory compliance